Successful commercialisation of locally fabricated bioceramics for clinical applications. - Fazan, Fazilah; Besar, Idris; Osman, Anuar; Samsudin, Abdul Rani; Khalid, Kamarul Ariffin (2008)
This paper chronicled the development of a locally produced bone graft substitute based on calcium phosphate bioceramics called "GranuMaS--from concepts to clinics, and finally to its successful commercialization all within 5-year duration. It was a Prioritized Research (PR) collaborative project of 5 institutions namely SIRIM, ANM, USM, UKM and IIUM, funded by MOSTI to the amount of approximately RM2.5 millions under RM8. This paper also highlighted the requirements needed in terms of technical expertise/manpower, facilities and infrastructure, and government/institutional supports, as well as the challenge faced in developing and commercializing such product.